Faktor-Faktor Pendidikan Dalam Pandangan Al-Qur’an dan Hadis - Wirnawaty Pilomango; Kasim Yahiji; Rahmin Thalib Husain; Ilyas Daud (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This paper aims to determine educational factors from the perspective of the Al-Qur'an and Hadith. Several factors in education are Human Factors, Educator Factors, Student Factors, Islamic Education Material and Method Factors, Learning Media Factors. This research uses a library research method. Literature review is a research technique by conducting searches regarding the concept of Islamic Education factors in terms of the Al-Qur'an and Hadith. Literature reviews are an important tool in contact reviews because literature is very useful and helps provide context and meaning to the writing that is being written. One of the educational factors reviewed from the Al-Qur'an is the human factor, which includes; can be caused by a leader, especially because of his leadership style, personnel who try to maintain rigid rules and arise because of individual personality traits, namely egoistic, temperamental, fanatical and authoritarian attitudes. Then the educational factor that is viewed from the Hadith is the parental education factor, where education in the family is the first and main education for children. Meanwhile, parents are the leaders of the family who are responsible for the safety of their children both in this world and in the afterlife, because children are not born but are born in a state of nature. So parents are obliged to educate their children. Children follow the example of their family members, their father, their mother or their siblings, so parents in the family must pay attention to their children and educate them. Parents are interested in the progress and development of their children, people always hope that their sons and daughters will be better than their parents.